The corticostriatal junction: a crucial region for forebrain development and evolution. - Molnár, Z; Butler, AB (2002)
Most parts of the brain are conserved across reptiles and birds (sauropsids) and mammals. Two major qualitative differences occur in the upper part, or pallium, of the telencephalon, the most rostral part of the brain. Mammals have a six-layered neocortex and also exhibit a different morphological organization in the lateral half, or sector, of their pallium than do sauropsids. These differences of lateral pallial construction may derive from small but crucial differences in migration patterns of neuronal precursors generated at or above the corner of the lateral ventricle, the corticostriatal junction (CS). Sauropsids have a large structure, the dorsal ventricular ridge, that is proliferated from this region, and its anterior part (ADVR) receives ascending projections from the dorsal thalamus. Mammals have multiple structures in this same region-the lateral part of neocortex, amygdala, and claustrum-endopiriform formation. We propose here that, as the degree of development of structures that form the deeper tier of the pallium varies across the stages of embryology and across phylogeny, mutations may have occurred during evolution at the origin of mammals that had profound consequences for the fate of neural populations generated in the region of the CS and its neighboring pallial germinal zone.